(untitled) (Fiep Bulletin - online, 2014)
The Brazilian society demands a quality education. Based on that prerogative, the present article looks to contemplate concerning the directions taken by the national education. For so much, the descriptive nature methodology was used, based on a literature revision that approached the historical of the school Physical Education, the traverse themes and analyze it of the dicotomy among the Traditional and Contemporary Physical Education. In that direction, was noticed that, to apply a Contemporary pedagogy it is of great relevance to discuss points, such as: the contents of conceptual nature, procedimental and atitudinal and the change of paradigm of the sport and the biological ones in the search of the discipline for the body. Today, the Physical Education should contribute to the intellectual activity, returned to a reflection on the corporal culture of the movement, by means of use the thematic axes, intensivity of the sports, inclusion and that incorporates the elements of our society. However, it is recommended fundamentally a change of the professionals’ attitude and of the own society, with the proposal of debates, seminars in congresses in university level, so that the professionals of the Physical Education can become aware of that new proposal that alters the paradigms of the Physical Education substantially.